An introduction to English grammar - Nelson, Gerald; Greenbaum, Sidney (b)
An introductory descriptive survey, intended for for students, teachers and general readers, which offers coverage of grammatical topics with sections on spelling, punctuation and exercises
Includes references and index.
Keywords: English language Grammar